Emplotment i historyczność: Tropy narracyjne dyskursu historycznego w Prabandhakośa - Jain, Abhishek (My University, 2021)
Prabandhakośa, będąca przedmiotem niniejszej dysertacji, to średniowieczna historiografia indyjska napisana w sanskrycie przez Rājaśekharasūri w 1348 roku n.e. Dzieło składa się z dwudziestu czterech prabandha, czyli historii z życia różnych słynnych postaci historycznych. Część I „Wprowadzenie” rozpoczyna się od przedstawienia historii gatunku prabandha, a także omawia historyczne okoliczności powstania Prabandhakośi, tłumacząc i analizując kolofon tekstu. Następnie opisuje i podsumowuje zawartość 24 historii życia. Na potrzeby zbadania tekstu wybrano cztery prabandha z Prabandhakośa do specjalistycznej analizy i tłumaczenia. Stosownie uargumentowano tu, dlaczego te cztery prabandha zostały wybrane jako reprezentatywne dla czterech części tekstu. Pierwszy rozdział rozprawy kończy się szczegółową historią badań nad Prabandhakosią wraz ze wstępem do istniejących wydań tekstu oraz niektórych znanych rękopisów sanskryckich. Poczynając od części II, „Klasyczny schemat sanskrycki jako abhītihāsa”, rozprawa przechodzi w analizę teoretyczną Prabandhakośi zawartą w rozdziałach 2 i 3. Dyskusję teoretyczną otwiera analiza modelu struktury fabuły przedstawionego w Natjaśastrze, który jest aplikowany do czterech narracji prabandha wybranych z Prabandhakośi w celu zbadania historyczności zawartej w tekście rozumianym jako dyskurs historyczny. W celu zaznaczenia, że teoretyczne pojęcia analizowane w rozprawie odnoszą się konkretnie do indyjskiego kontekstu kulturowego, w niniejszym opracowaniu zaproponowano neologizmy sanskryckie lub hindi dla wybranego zestawu terminów zaczerpniętych z teorii Haydena White. Część III rozprawy zawiera angielskie tłumaczenia czterech prabandha wybranych do tego badania wraz z wyczerpującymi komentarzami na temat całej stosownej terminologii i informacji faktograficznych znajdujących się w każdej narracji. Podsumowując, rozprawa przedstawia Prabandhakośę jako ważne i reprezentatywne dzieło literatury dźajn prabandha jako gatunku historiograficznego. Pokazuje indyjską metodę analizy struktury fabularnej narracji prabandh i dowodzi, że struktura fabuły jest ważnym elementem wewnętrznej konstytucji tekstu jako autentycznego pisma historycznego.

The Jain prabandha genre belongs to the late medieval Sanskrit literature written by Śvetāmbara Jain monk-authors. These literary compositions can be recognized as forms of medieval Indian historiography. One of the major works of this genre is the Prabandhakośa written in Sanskrit by Rājaśekhara Sūri in 1348 CE. This text serves as the case study for this dissertation. The title of the text, Prabandhakośa, means “A Collection of Life-Stories. ” The work contains twenty-four prabandhas or 'life-stories' dealing with the lives of different famous historical individuals. In order to introduce the text, the first chapter of the dissertation, found in Part I “Introduction,” starts by presenting the history of the prabandha genre. It is shown that the word prabandha is attested from the Vedic literature onwards in the general literal sense of the word referring to something that is well-tied together or having continuity. With the Nāṭyaśāstra composed in the early centuries CE, the word appears for the first time in a more figurative sense of a “literary composition.” This is also the sense that the word prabandha has in the 7th-century CE treatise on poetics by Bhāmaha, the Kāvyālaṅkāra. From this usage of the Sanskrit word, prabandha is picked up as a loanword in several regional Indian languages, including Kannada, Telugu, Tamil, and Hindi, where it continued to be used in the general sense of a “literary composition” or “literary work,” which at times is equated with the term kāvya, 'literature' or 'poem'. These developments are delineated in some detail in the chapter. In the late medieval Jain Śvetāmbara tradition, however, the word prabandha took on a special meaning, in that it became the name of a particular genre of literary writing. The prabandha genre, which is specific to Śvetāmbara Jainism, is a writing of 'biographies' or 'life-stories' of individuals of recent history. The author of the Prabandhakośa, Rājaśekhara Sūri, himself defines the term as referring to written life-stories of individuals who lived after the Jain monk Āryarakṣita around the 2nd century BCE. When defined in this way, it is possible to identify 21 texts of the Śvetāmbara prabandha genre composed in the period 1243 till 1593 CE, most of which have the word prabandha explicitly in their titles. Many of these texts contain life-stories of multiple historical individuals and the Prabandhakośa is thus a collection of 24 such biographies.
Emplotment and Historicity: Narrative Modes of Historical Discourse in the Prabandhakośa
Wydział Neofilologii
Keywords: prabandha; historical discourse; emplotement; narrative; modes; Jainism